The Relationship Between Social Media Use and Adolescent Sexual Behavior - Astri, Shelsi Yulia; Astuty, Delfriana Ayu; Nurhayati, Nurhayati (GLOBAL HEALTH SCIENCE GROUP, 2024)
During adolescence there are several problems, one of which is the period of sexuality. The causes of sexual behavior in teenagers include providing cellphone facilities, the use of social media which is often used by teenagers to spend hours viewing and commenting on posts on social media. This research aims to determine the relationship between social media use and adolescent sexual behaviour. This research uses quantitative research with a correlation analytical design with a cross sectional approach. The sample in this study was 75 people from class XII of SMA Darussalam Medan. The sample was taken using a purposive sampling technique with a sample size of 75 people. Data collection was carried out through a questionnaire, containing written questions that were submitted to respondents to be answered. Data analysis includes univariate and bivariate analysis, using the chi-square test to see the relationship between variables. The results of this study show that the proportion of respondents who have high levels of sexual behavior is dominated by the female gender. The results of using social media sites show a significant p value = 0.044 with a risk of adolescent sexual behavior of 0.138 times as a result of exposure to the use of social media sites. There are significant results on the use of social media and adolescent sexual behavior with a p value = 0.044, so it can be concluded that there is a relationship between social media use and adolescent sexual behavior.